Balance bike injuries: A retrospective chart review. (12th April 2022) - Oishi, Takatoshi; Amagasa, Shunsuke; Hayashi, Yukiko; Uematsu, Satoko
Abstract : Aim: To determine the characteristics of balance bike injuries. Methods: This study retrospectively identified patients injured while riding a balance bike and treated at one paediatric emergency department in urban Japan, from February 2015 to July 2020. Data extracted were patient age and sex, circumstances and location of the injury occurrence, helmet use, adult supervision, injury type and body site, treatment and emergency department disposition. Based on these data and the balance bike manual instructions, cases were classified as correct and incorrect balance bike use. Results: The study assessed 78 patients, age 2–6 years (median 3 years; 73% male). Of these 78 patients, 63 did not follow balance bike manual instructions (80.8%); 34 (43.6%) were injured while riding in prohibited places of use; 45 (57.7%) were injured in prohibited situations of use; and 37 (47.4%) were injured despite adult supervision. A total of 124 injuries were noted; the most common injured body site was the face (49 injuries, 39.5%), followed by the head (40 injuries, 32.3%). Most injuries were contusions and abrasions (65 injuries, 52.4%). More serious injuries were intensive care unit admission with intracerebral haemorrhage (1 patient) and lateral condyle fracture with surgical repair (1 patient). Conclusions: Most of the 78 balance bike injuries (76 patients) were mild; 2 were more severe and required intensive care unit admission or operation. Parents must be aware of the rules and instructions for balance bike use and ensure that their children can use the balance bike correctly.